Small-scale flux transfer events formed in the reconnection exhaust region between two X lines - Hwang,KJ; Sibeck,DG; Burch,JL; Choi,E; Fear,RC; Lavraud,B; Giles,BL; Gershman,D; Pollock,CJ; Eastwood,JP; Khotyaintsev,Y; Escoubet,P; et al. (Journal of Geophysical Research: Space Physics, 2018)
We report MMS observations of the ion-scale flux transfer events (FTEs) that may involve two main X lines and tearing instability between the two X lines. The four spacecraft detected multiple isolated regions with enhanced magnetic field strength and bipolar Bn signatures normal to the nominal magnetopause, indicating FTEs. The currents within the FTEs flow mostly parallel to B, and the magnetic tension force is balanced by the total pressure gradient force. During these events, the plasma bulk flow velocity was directed southward. Detailed analysis of the magnetic and electric field and plasma moments variations suggests that the FTEs were initially embedded within the exhaust region north of an X line but were later located southward/downstream of a subsequent X line. The cross sections of the individual FTEs are in the range of ~2.5–6.8 ion inertial lengths. The observations suggest the formation of multiple secondary FTEs. The presence of an X line in the exhaust region southward of a second X line results from the southward drift of an old X line and the reformation of a new X line. The current layer between the two X lines is unstable to the tearing instability, generating multiple ion-scale flux-rope-type secondary islands.